Jaringan dan Komentar Viral Marketing Pantene Indonesia Miracles Hair Supplement Baru Pada Akun Youtube Pantene Indonesia - Francisca Bertha Vistika Putri; Daniel Susilo; Agustinus Rusdianto Berto (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2022)
Viral marketing is the main goal of marketers in conveying messages so that their products or services can be seen by many people. However, viral marketing does not always get a positive response from the public. In this study, the researcher wanted to see how the network was formed so that the advertisement for the New Pantene Miracles Hair Supplement could go viral and comment on the advertisement on Youtube. Apart from that, we also saw the impact of the Viral advertisement after several months of being broadcast on Youtube on other media such as Twitter. That way, this research is expected to be a reference for marketers in creating viral marketing. This research uses the social network analytic method by analyzing Youtube networks and comments with the help of the Netlytic and Gephi applications. The results found that the network on Youtube did not form a large group because many comments were independent, while in terms of comments tended to be positive. While on Twitter, a small network of conversations is still formed after three months of advertisements. However, the comments are more in the direction of the Pantene campaign about tired hair and the network is not large considering the number of people who post this content is not as many as when the ad was running.